Tradisi Pembacaan Manaqib Syekh Samman Karya Syekh Azhari pada Upacara Nimbang Bunting di Palembang - Saputra, Roki (Universitas Al Azhar Indonesia, 2024)
The tradition of reciting Manaqib Syekh Muhammad Samman in Palembang has deep historical and religious roots, especially in the Nimbang Bunting traditional ceremony. This tradition reflects the religious identity of the Palembang people while preserving ancestral heritage which is a means of prayer and preserving the community's moral values. This Research aims to describe the tradition of reading the Manaqib of Sheikh Muhammad Samman, authored by Sheikh Azhari, in the Nimbang Bunting ceremony in Palembang. The study uses a qualitative approach, with data collected through direct observation during the ceremony and interviews with Manaqib readers and ceremony participants. The data were analyzed descriptively to illustrate this tradition. The research findings indicate that reading the Manaqib by specific individuals (women), known as Maco Hol, is the core of the Nimbang Bunting ceremony. The readings are conducted using Latin-Malay scripts, which most participants understand. The ceremony also involves symbols, hopes, and prayers associated with the Manaqib readings. These findings highlight the importance of the tradition of reading the Manaqib of Sheikh Muhammad Samman in the culture and life of the Palembang community. This tradition not only serves as a form of respect for the Sufi figure but also plays a role in strengthening the cultural and religious identity of the local community. The results of this study are expected to provide deeper insights into this tradition and serve as a reference for future research.Keywords - Manaqib, Nimbang Bunting, Sheikh Muhammad Samman, Tradition.